EDUKASI DAN KOLABORASI PENANGANAN LIMBAH PLASTIK MELALUI TeeFILIC DI SMP TELKOM BANDUNG - AMALIYAH ROHSARI INDAH UTAMI; Diyana Afdhila; Septiana Dwika Pangestu; Alit Munawar Holil (Jurnal Sinergitas PKM & CSR, 2025)
Program TeeFILIC (The Importance of Collaboration and Education in Addressing Plastic Waste) mengintegrasikan edukasi literasi lingkungan dan aksi partisipatif bertema limbah plastik melalui kemitraan Prodi Teknik Fisika Universitas Telkom dan SMP Telkom Bandung, yang diperkaya inisiatif Aksi Bumi untuk membiasakan pemilahan, kampanye, serta praktik pengelolaan sampah di lingkungan sekolah. Intervensi dirancang berlapis mencakup lokakarya sains plastik dan mikroplastik, demonstrasi pemilahan di sumber, aksi bersih–pilah dengan kantong terlabel, kompetisi poster edukatif, serta klinik kolaborasi guna menyusun rencana tindak lanjut bersama guru dan pengurus siswa. Indikator keberhasilan meliputi tingkat partisipasi pelajar–guru–mahasiswa, rasio volume sampah terpilah organik dan plastik, kualitas materi kampanye, serta komitmen implementasi rutin dan penetapan duta lingkungan. Hasil menunjukkan keterlibatan ratusan siswa dan pendidik, penguatan pemahaman bahaya mikroplastik, serta peningkatan praktik pemilahan yang dibuktikan melalui rekap kantong pada aksi inti dan dokumentasi visual terstandar. Jejaring kolaborasi dan dukungan institusional memungkinkan integrasi modul 2×45 menit ke pembelajaran/ekstrakurikuler dan replikasi ke sekolah jejaring. Kontribusi pada SDGs 4 tercermin dari peningkatan literasi dan praktik belajar aktif, sedangkan SDGs 17 tercapai melalui kemitraan multipihak yang berkelanjutan. Model ini menunjukkan jembatan efektif dari pengetahuan ke perubahan perilaku, dengan potensi skalabilitas dan pelaporan akuntabel di prosiding PKM-CSR. The TeeFILIC (The Importance of Collaboration and Education in Addressing Plastic Waste) program integrates environmental literacy education and participatory plastic waste–themed activities through a partnership between the Physics Engineering Study Program at Telkom University and SMP Telkom Bandung, enhanced by the Earth Action initiative, which emphasizes regular waste sorting, campaigns, and management practices within the school setting. The intervention was structured in multiple stages, including science workshops on plastics and microplastics, on-site waste sorting demonstrations, clean-up actions using labeled waste bags, educational poster competitions, and collaborative clinics to develop follow-up plans with teachers and student leaders. Success indicators included levels of participation of students, teachers, and university mentors; the ratio of sorted organic and plastic waste; the quality of campaign materials produced; ongoing commitment to routines; and the appointment of environmental ambassadors. The results demonstrated the involvement of hundreds of students and educators, a greater understanding of microplastics hazards, and improved waste sorting, as documented by a recap of bag counts during key actions and standardized visual records. Collaborative networking and institutional support enabled the integration of a two-session (2 × 45 minutes) module into both curricular and extracurricular learning, facilitating its replication across partner schools. Contributions to SDG 4 are reflected in the advancement of literacy and active learning practices, while SDG 17 is achieved through sustainable, multi-stakeholder partnerships. This model demonstrates an effective bridge from knowledge to behavioral change, with notable potential for broader implementation and robust accountability in PKM-CSR conferences.